A study of Flow and Its Factors Towards Compulsive Buying Based on Player Behavior of Mobile Legends In-Game Items - Lapasha, Brian Mario; Tanuarto, Martinus Y; Wiranata, Sujadi; Burhamsyah, RM Bryan (Dinasti Publisher, 2024)
Purpose - Examining flow of Mobile Legends player correlating to compulsive buying on in-game items and factors related to flow such as enjoyment, skills, difficulty and avatar identification. Methodology/design - The data were obtained using surveys distributed via several gaming communities' group chats and channels including Discord and WhatsApp, where they were collected from 275 respondents. Findings - The research revealed that flow does have an impact on compulsive buying. Additionally, challenge and telepresence have a favorable impact on flow where skill and fun were not encouraged. Meanwhile, avatar identification is positively impacted by avatar attractiveness and personalization. Avatar identification thus has a favorable impact on flow. This study focused on the connection between compulsive shopping, avatar identity, and player behavior. Originality/value - The research hypotheses for this study can be summed up as: How can flow positively affect compulsive buying? Therefore, this study aims to identify and examine its significance through the variables of player behavior and avatar identification, which are the stimuli of flow in games.